Arab Culture and Organisational Context in Work-Life Balance Practice for Men and Women: A Case Study from Gaza, Palestine - Mahmoud Abubaker; Chris Adam-Bagley (Societies)
This paper examines types of WLB (Work–Life Balance Policies) that have emerged in research in Western countries, and compares their applicability for male and female employees in Arab countries in general, and in Gaza, Palestine in particular. A qualitative study has been undertaken with employees of telecommunication companies, with thematic analysis to identify new kinds of WLB in an Arab culture. The WLB policies identified in the two companies were often quite different from those identified by Western researchers, and were guided by the religious principles of Islam, cultural factors, and the needs and aspirations of female employees. The international investors identified had adapted their policies to meet the cultural requirements of an Arabic society. This paper contributes to debates on the effectiveness of, and the need for culturally adapted WLB policies which try to meet the aspirations of women in developing countries. Additionally, this case study adds a new theoretical base, advocating the importance of WLB policies which are adapted to local cultural conditions in ways which also meet the aspirations of international business models. The WLB practices identified have not been described previously in any detailed study. The WLB policies and practices identified advocate for further research studies focusing on gender differences in the provision and take-up of WLB, using both qualitative and quantitative methodologies.